CA1 and CA3 differentially support spontaneous retrieval of episodic contexts within human hippocampal subfields - Halle R. Dimsdale-Zucker; Maureen Ritchey; Arne D. Ekstrom; Andrew P. Yonelinas; Charan Ranganath (Nature Communications, 2018)
Computational studies have hinted that hippocampal subfields represent information differently. Here, the authors show that when retrieving items that share an episodic context, subfield CA1 represent similarities between items whereas CA2/3/dentate gyrus represents item-unique features.